Severe acute respiratory syndrome coronavirus‐2: implications for blood safety and sufficiency. Issue 2 (23rd September 2020) - Kiely, Philip; Hoad, Veronica C.; Seed, Clive R.; Gosbell, Iain B.
Abstract : Background and Objective: Severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) is a novel coronavirus, first identified in China at the end of 2019 and has now caused a worldwide pandemic. In this review, we provide an overview of the implications of SARS‐CoV‐2 for blood safety and sufficiency. Material and Method: We searched the PubMed database, the preprint sites bioRxiv and medRxiv, the websites of the World Health Organization, European Centre for Disease Prevention and Control, the US Communicable Diseases Center and monitored ProMed updates. Results: An estimated 15%–46% of SARS‐CoV‐2 infections are asymptomatic. The reported mean incubation period is 3 to 7 days with a range of 1–14 days. The blood phase of SARS‐CoV‐2 appears to be brief and low level, with RNAaemia detectable in only a small proportion of patients, typically associated with more severe disease and not demonstrated to be infectious virus. An asymptomatic blood phase has not been demonstrated. Given these characteristics of SARS‐CoV‐2 infection and the absence of reported transfusion transmission (TT), the TT risk is currently theoretical. To mitigate any potential TT risk, but more importantly to prevent respiratory transmission in donor centres, blood centres can implement donor deferral policies based on travel, disease status or potential risk of exposure. Conclusion: The TT risk of SARS‐CoV‐2 appears to be low. The biggest risk to blood services in the current COVID‐19 pandemic is to maintain the sufficiency of the blood supply while minimizing respiratory transmission of SARS‐CoV‐19 to donors and staff while donating blood.